Microbial response mechanisms of organic nitrogen substitution for optimizing tobacco yield and quality: the key role of 50% organic nitrogen - Liang, Yongjin; Cheng, Wuyang; Peng, Bo; Xiao, Jinglin; He, Yi; Xiao, Heyou; Dai, Rongcheng; Huang, Qiu; Chen, Fei; Ling, Huarong; He, Shijie; Zhu, Ruixuan; et al. (Frontiers in Microbiology, 2025)
IntroductionPrecise matching of nutrient supply with plant demand in tobacco cultivation is crucial for achieving high yield and superior quality. Traditional chemical fertilizer application modes have obvious limitations, and although organic nitrogen substitution has become an important development direction, the determination of optimal substitution ratios and their microbial regulatory mechanisms still require in-depth research.MethodsBased on previous studies, this research established refined organic nitrogen substitution experiments with treatments of 40, 50, and 60% organic nitrogen substitution at two experimental sites, systematically evaluating the effects of different substitution ratios on yield and quality of tobacco, while analyzing differences in soil microbial community composition, function, and network correlations through 16S rRNA sequencing and network analysis.ResultsResults showed that organic nitrogen treatments significantly improved the agronomic traits, yield performance, chemical composition, and sensory quality of tobacco. The underlying microbial community mechanisms revealed that organic nitrogen application significantly enhanced soil microbial community diversity, enriched beneficial bacterial groups (Pseudomonadota, Actinomycetota, Bacteroidota, etc.), strengthened carbon and nitrogen cycling functions, and increased network complexity. Redundancy analysis demonstrated that the microbial communities under organic nitrogen treatments were closely associated with yield and quality traits such as potassium and total sugars. Among all treatments, the 50% organic nitrogen treatment performed optimally, achieving yield increases of 63.4 and 67.8% at two experimental sites respectively, with the best tobacco leaf chemical quality and sensory characteristics. This treatment also exhibited superior performance in microbial community structure and functional coordination, and the study found that 50% is the optimal substitution ratio for microbial response.DiscussionThis study confirmed that 50% organic nitrogen substitution constitutes the optimal fertilization scheme and revealed the underlying microbial response mechanisms by which this ratio optimizes tobacco quality, providing scientific guidance for precision fertilization of tobacco based on microbial theory.